Association of Respiratory Morbidities with Particulate Air Pollution in Delhi, India- A Prospective Study - Nandini Sharma; Pragya Sharma; M. P. George; Anil K. Singh; Ekta Arora (Preventive Medicine: Research & Reviews)
Background: Elevated levels of air pollution and long-term exposure can lead to detrimental health conditions, mainly affecting cardiorespiratory systems. Materials and Methods: A prospective observational study was conducted in five sampled hospitals in Delhi. A pre-designed, pre-tested, semi-structured questionnaire was filled out for each patient with data from hospital records. The admission rates were recorded daily over the study period along with the air quality with reference to particulate matter (PM). The trends of the hospital admissions for respiratory morbidity were corroborated with PM 2.5. Descriptive statistics and correlation amongst emergency admissions and air pollutants were analysed using Microsoft Excel. The impact of air quality on the rate of hospitalisation due to respiratory conditions was projected by mathematical modelling. Results: The rate of hospitalisation due to bronchial asthma, chronic obstructive pulmonary disease, bronchitis and lower respiratory tract infections was found to be directly proportional to an increase in PM2.5. Conclusion: The healthcare system is increasingly strained and thus, the additional burden due to rising air pollution needs to be prevented by making people aware about the methods of reducing air pollution.